Malay language enhancement carnival benetted UMP foreign students - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP)’s Centre for Modern Languages & Human Sciences (CMLHS) organised the Enhancement of Malay Language Carnival and Community Service involving 35 of its foreign undergraduates who were from Yemen, Egypt, Iraq, Syria and Sudan, and 444 students from Sekolah Menengah Kebangsaan Seri Bera.